The Effect of Use of Employee Self Servce (Ess) on the Performance of PT Employees. Rp - Anggraeni, Nevi; Fa’uzobihi, Fa’uzobihi; Santosa, Kaffah Imanuddin MR (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to analyze the effect of use of Employee Self Servive (ESS) on the performance of PT.RP employees. Employee Self Servive (ESS) is an important factor in human resource management that can facilitate employee performance and productivity in the current era of digitalization. This research used a quantitative approach with a saturated sampling method on 34 employees from various levels at PT. RP. Data is collected through a structured questionnaire that measures employee perceptions of usage Employee Self Servive (ESS) and employee performance. Data analysis was carried out using a simple linear regression method to test the research hypothesis. The results of this research show that there is an influential Employee Self Servive (ESS) regularly partial impact on the performance of PT.RP employees. These findings imply the importance for companies to design and implement Employee Self Servive (ESS) which is comprehensive and user friendly to improve employee performance. This research also recommends the need for regular evaluation of employee Self Servive (ESS) to ensure its effectiveness in encouraging optimal employee performance.